Entre a mesa e a cruz: Discursos sobre espiritismo no Maranhão no limiar do século XX - CARVALHO NETTO, Carlos Alberto de (2017)
Spiritism comes under three main names: philosophy, religion, and science; its identity base since the codification by Hippolyte Leon Denizard Rivail, aka Allan Kardec, a French intellectual who gave doctrinal form to a group of practices and spiritualist beliefs in vogue in the nineteenth century. The Spiritist identity was built in the antithesis between two concepts: religion and science; Spiritism would be the sign of conciliation between the two. Through discourse analysis of newspapers and publications from Maranhão, between the 1910s and 1930s, linked to Spiritist groups and the Catholic Church, we sought to approach the construction and uses of concepts of science and religion from Spiritism, while legitimizing characteristics of doctrine. We also tried to understand the evolution of the term Spiritism as a concept and its subsequent resemantiation, in an attempt to contribute to the understanding of the complexity of the Brazilian religious scene.